Decentralising competences in multi-level systems: insights from the regulation of genetically modified organisms - Tosun, Jale; Hartung, Ulrich (West European politics, 2017)
The adoption of Directive 2015/412 marks a turning point in policy-making in the European Union since for the first time the legal competence for a regulatory area has been passed from the EU to the member states. The member states can now request their territory to be excluded from authorisation for genetically modified organisms (GMOs) for commercial cultivation. In the first step of the analysis, the article shows that higher levels of public support for GMOs decrease the likelihood of member states filing an opt-out request, while controlling for other potential explanatory factors. In the second step, it concentrates on the controversy between the federal and the state level in Germany regarding the transposition of the new directive. It is found that the directive offers some degree of strategic opportunity for pro-GMO political parties to pursue a regulatory approach that would otherwise be impeded by negative public opinion.
Gesehen am 14.02.2018